Improvement of pedagogical skills of teachers of a foreign language in reference to training process, based on innovative information technologies (Pedagogy of Higher and Secondary Education, 2013)
Poberezhna N. O. Improvement of pedagogical skills of teachers of a foreign language in reference to training process, based on innovative information technologies.The article deals with didactic and methodological aspects of modern pedagogical system and pedagogical activity in teaching foreign languages in the conditions of informatively-educational environment.
Keywords: pedagogical excellence; information competence; informatively-educational environment of higher educational establishment